Biologic variability and correlation of platelet function testing in healthy dogs. (23rd September 2015) - Blois, Shauna L.; Lang, Sean T.; Wood, R. Darren; Monteith, Gabrielle
Abstract : Background: Platelet function tests are influenced by biologic variability, including inter‐individual (CVG ) and intra‐individual (CVI ), as well as analytic (CVA ) variability. Variability in canine platelet function testing is unknown, but if excessive, would make it difficult to interpret serial results. Additionally, the correlation between platelet function tests is poor in people, but not well described in dogs. Objectives: The aims were to: (1) identify the effect of variation in preanalytic factors (venipuncture, elapsed time until analysis) on platelet function tests; (2) calculate analytic and biologic variability of adenosine diphosphate (ADP) and arachidonic acid (AA)‐induced thromboelastograph platelet mapping (TEG‐PM), ADP‐, AA‐, and collagen‐induced whole blood platelet aggregometry (WBA), and collagen/ADP and collagen/epinephrine platelet function analysis (PFA‐CADP, PFA‐CEPI); and (3) determine the correlation between these variables. Methods: In this prospective observational trial, platelet function was measured once every 7 days, for 4 consecutive weeks, in 9 healthy dogs. In addition, CBC, TEG‐PM, WBA, and PFA were performed. Results: Overall coefficients of variability ranged from 13.3% to 87.8% for the platelet function tests. Biologic variability was highest for AA‐induced maximum amplitude generated during TEG‐PM (MAAA ; CVG = 95.3%, CVI = 60.8%). Use of population‐based reference intervals (RI) was determined appropriate only for PFA‐CADP (index of individuality = 10.7). There was poor correlation between most platelet function tests. Conclusions: Use of population‐based RI appears inappropriate for most platelet function tests, and tests poorly correlate with one another. Future studies on biologic variability and correlation of platelet function tests should be performed in dogs with platelet dysfunction and those treated with antiplatelet therapy.